NICKEL IONS REMOVAL FROM AQUEOUS SOLUTIONS USING SAWDUST AS ADSORBENT: EQUILIBRIUM, KINETIC AND THERMODYNAMIC STUDIES - Faisal Muhaisen, Lahieb (Journal of Engineering and Sustainable Development, 2017)
This work is concentrate on removal of some environmentally relevant contaminants, such as nickel ions from simulated wastewater by sawdust low- cost natural sorbents. Sorption batch tests were investigated in the removal process at initial concentration of nickel ions (100 mg/l). Equilibrium, kinetics and thermodynamic studies were investigated for the removal process. Parameters affect as pH, amount of sawdust, contact time and temperature were studied. The uptake capacity was 12.5 mg/g; also FTIR demonstrated that carboxyl and hydroxyl groups were involved in the adsorption of the metal ions. The results indicated that adsorption is an endothermic process and rate of removal increased with increase temperature.